Lean Tools for Product Improvement: A Case Study - Zbigniew SKUZA; Rafal PRUSAK (Communications of International Proceedings, 2023)
The dynamically changing market environment and strong competition require companies to continuously improve their products and meet, and preferably exceed, customers’ requirements. Improvement processes may concern all areas of an organization’s activity and result from the nature of its operations. Among the many methods and ways to support the development of a given economic entity, one of the most popular tools is Lean Management. The topic of using Lean tools from the point of view of improving enterprise operations, despite its wide spread, still requires deeper analysis - especially from a practical point of view. The information obtained from this type of analysis may be useful for both theoreticians and practitioners. The aim of the article is to present the possibilities offered by Lean tools in the product improvement process. The article presents is a case study and discusses the work of a team who studied a household appliance production line in terms of the number and types of recognized complaints using the Kaizen, 5W1H, 4M, Poka-Yoke and 5S methods.
Keywords: Lean Management concept; Lean Manufacturing; Lean tools; product improvement